2015
DOI: 10.2903/j.efsa.2015.3957
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the essential composition of total diet replacements for weight control

Abstract: Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver a scientific opinion on the essential composition of total diet replacements for weight control. Total diet replacements for weight control are intended to induce a substantial energy deficit in overweight or obese adults who wish to lose weight and replace the whole diet in the context of energyrestricted diets for weight reduction. In this opinion, the Panel proposed a min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 100 publications
(147 reference statements)
0
16
0
Order By: Relevance
“…According to the European Food Safety Authority (EFSA), VLCKDs are formulated foods that, when used as instructed by the manufacturer, replace the whole diet (total meal replacement) and provide less than the minimum amount of energy provided by low-calorie diets. In particular, VLCKD is characterized by an energy intake of 600 kcal per day with 50%–60% of energy intake derived from proteins, 20%–30% from lipids, and 20% from carbohydrates [35]. All nutritional requirements were met using five to six formulated meals a day containing about 15–18 g of high biological value protein preparations, 4 g carbohydrates, and 3 g fat.…”
Section: Methodsmentioning
confidence: 99%
“…According to the European Food Safety Authority (EFSA), VLCKDs are formulated foods that, when used as instructed by the manufacturer, replace the whole diet (total meal replacement) and provide less than the minimum amount of energy provided by low-calorie diets. In particular, VLCKD is characterized by an energy intake of 600 kcal per day with 50%–60% of energy intake derived from proteins, 20%–30% from lipids, and 20% from carbohydrates [35]. All nutritional requirements were met using five to six formulated meals a day containing about 15–18 g of high biological value protein preparations, 4 g carbohydrates, and 3 g fat.…”
Section: Methodsmentioning
confidence: 99%
“…The fact that women pay more attention to their diet is supported by other studies: Ervin et al [18] observed that women consumed more fruit, vegetables, legumes, and oils than men. Additionally, they drank less alcohol and their intake of calories from solid fats and sugars was lower [18]. Other studies also showed that women had healthier diets: they ate more meals (85% of women and 79% of men ate minimum 3 meals per day), and consumed fruit and vegetables more frequently.…”
Section: N=566 N=750mentioning
confidence: 73%
“…For example, Poland is in 9 th place among the EU countries in terms of the number of daily smokers and percent of people with excess body weight increases since 1996. In addition, the problem is very low consumption of fruit and vegetables and low physical activity [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…-VLCKD: in agreement with the European Food Safety Authority (EFSA) [18], this diet contained a minimum protein content based on a Population Reference Intake for protein adjusted for the overweight (≥75 g/day), a very limited carbohydrate content (30–50 g/day), a fixed amount of fats (20 g/day mainly from olive oil), and micronutrients to fulfill the Dietary Reference Intake (DRI) (Table 1).…”
Section: Methodsmentioning
confidence: 99%